Aguardente tiquira do Maranhão: Oportunidades e Entraves para a Implementação de uma Indicação Geográfica - NASCIMENTO, Jaqueline Silva (2023)
Geographical Indications (GIs) are established as a form of protection for products or services that have become known over time because they come from a particular region or location. Such protection, in turn, with regard to the legal sphere, stems from the fact that Geographical Indications constitute an instrument of Industrial Property. In this work, a survey of supporting elements was presented for the recognition of the Tiquira brandy as the first Geographical Indication in the State of Maranhão. The present work aimed to identify the attributes of quality, typicality, tradition and cultural heritage to obtain the GI registration for the Tiquira brandy, in the region of the Microregions of Lençóis Maranhenses, Chapadinha and Baixo Parnaíba Maranhense, which meets the requirements for the registration of Geographical Indication. This is a quali-quantitative, bibliographical, documental research, built from secondary data considered relevant for proving the product's notoriety. As a result, this study brings elements that show that Tiquira brandy, in the state of Maranhão, has the potential to be recognized as a Geographical Indication and that initially it must be registered in the Indication of Origin modality with the National Institute of Industrial Property (INPI), considering that Maranhão is known for the production of Tiquira, derived from the alcoholic fermentation of beijus, a distilled beverage with a high ethyl alcohol content, of indigenous origin, whose raw material is cassava. Finally, the recognition of GI Tiquira would provide greater competitiveness in the national and international market, add value to the product and encourage extractivists to conserve the traditional sustainable method of production, but for this to happen it will be necessary to mobilize producers/extractors.